Deep Vein Thrombosis in Europe—Health-Related Quality of Life and Mortality. (20th November 2019) - Monreal, M.; Agnelli, G.; Chuang, L. H.; Cohen, A. T.; Gumbs, P. D.; Bauersachs, R.; Mismetti, P.; Gitt, A. K.; Kroep, S.; Willich, S. N.; Van Hout, B.
Objectives: Deep vein thrombosis (DVT) is a major health-care burden in Europe, but exact estimates are lacking. This study reports results from the PREFER venous thromboembolism (VTE) study concerning health-related quality of life (HrQoL) and mortality of patients with DVT. Methods: PREFER VTE was a prospective, observational study, conducted in 7 European countries, designed to provide data concerning treatment patterns, resource utilization, mortality, and QoL. First-time or recurrent patients with DVT were followed at 1, 3, 6, and 12 months. Health-related QoL—as measured by the EuroQoL 5-Dimension 5-Level instrument ( EQ-5D-5L)—was analyzed using Tobit regression with repeated measures, assessing the impact of baseline characteristics stratified by cancer activity. Mortality was analyzed using logistic regression. Results: At baseline, patients with DVT had a 0.14 lower EQ-5D-5L index score (0.72 for total sample) compared to the reference UK population (0.85). The EQ-5D-5L index score improved from baseline to 12 months in patients with active cancer (from 0.70 to 0.79) and those without (0.72-0.87); 7.3% died within a year, a 5.2% excess mortality compared to the age- and gender-adfjusted general population. The 12-month mortality rate of DVT varied between 2.9% in the pooled data from Germany, Switzerland, or Austria and 15.4% in Italy. Furthermore, the mortality rate differed between patients with active cancer and those without (42.9% vs 4.7%). Conclusions: Deep vein thrombosis is associated with a substantial burden of illness in terms of HrQoL at baseline, which following treatment normalizes after 12 months and has a significant mortality rate. In addition, active cancer has a significant impact on mortality and the HrQoL of patients with DVT.